(untitled) (Acta Scientiarum. Biological Sciences, 2020)
In addition to several local pathophysiological consequences, intestinal injury that is caused by ischemia and reperfusion can result in the development of lesions in remote organs. Curcumin has therapeutic potential because of its antiinflammatory and antioxidant effects. The present study evaluated the effects of curcumin on oxidative and inflammatory parameters in the liver and kidneys in rats that were subjected to intestinal ischemia and reperfusion. The rats were subjected to 45 min. of ischemia followed by 7 days of reperfusion and treated daily with 60 mg kg-1 curcumin. The liver and kidneys were collected, weighed, and biochemically analyzed. Intestinal ischemia and reperfusion increased levels of lipid hydroperoxide (LOOH), decreased levels of reduced glutathione (GSH), and increased the enzymatic activity of superoxide dismutase (SOD), glutathione S-transferase (GST), and myeloperoxidase (MPO) in the liver. Intestinal ischemia and reperfusion decreased kidney weight and increased GST activity in the kidneys. Curcumin prevented these changes in the liver and kidneys. Intestinal ischemia and reperfusion mainly affected the liver, promoting inflammation and oxidative stress. The kidneys underwent repair much earlier than the liver, in which they did not present alterations of MPO or main parameters of oxidative stress after 7 days of reperfusion. Treatment with curcumin had beneficial effects, ameliorating or even preventing injury that was caused by intestinal ischemia and reperfusion in the liver and kidneys in rats